Gallium-doped platinum-based ordered alloy catalyst as well as preparation method and application thereof

Through the preparation method of gallium-doped platinum-based ordered alloy catalyst, the consistency and controllability of platinum-based alloy catalysts in the industrial amplification process are solved, and high-efficiency and low-cost catalyst production is achieved, and the performance of oxygen reduction reaction is improved.

CN120485834APending Publication Date: 2025-08-15GEM CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510743666.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

The existing platinum-based alloy catalysts perform well in the laboratory stage, but it is difficult to maintain batch consistency and controllability during the industrial amplification process. The traditional preparation methods are complex and costly, making it difficult to achieve large-scale commercial application.

Method used

The gallium-doped platinum-based ordered alloy catalyst is adopted, and the preparation method combined with impregnation method and ball milling method is used to use the atomic radius of the gallium element to be smaller than the transition metal element, and the intermetal ordered alloy is formed in the platinum-based alloy, adjust the adsorption strength of the oxygen reduction reaction intermediate on the Pt surface, improve the ORR performance of the catalyst, and achieve large-scale production through a simple high-temperature calcination process.

Benefits of technology

It realizes high performance and large-scale production of platinum-based alloy catalysts, improves the catalytic activity and stability of oxygen reduction reactions, reduces production costs, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120485834A_ABST
    Figure CN120485834A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalysis, and provides a gallium-doped platinum-based ordered alloy catalyst and a preparation method and application thereof.The gallium-doped platinum-based ordered alloy catalyst comprises a carbon carrier and active nanoparticles dispersed on the surface of the carbon carrier; the active nanoparticles comprise an intermetallic ordered alloy composed of Pt and a transition metal M, and Ga is doped in the intermetallic ordered alloy. The gallium element with smaller atomic radius is used for doping, so that crystal lattices can be further shrunk, the adsorption strength of the Pt surface to an oxygen reduction reaction intermediate is adjusted, and the ORR performance of the catalyst is effectively improved; according to the preparation method, the catalyst is prepared in a manner of combining an impregnation method, a ball milling method and a calcination method, manual operation is less, the process is simple, the cost is easy to reduce, and batch production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalysis and relates to a gallium-doped platinum-based ordered alloy catalyst and a preparation method and application thereof. Background Art

[0002] As one of the clean, efficient and renewable forms of energy, hydrogen energy has received widespread attention and research around the world in recent years. Fuel cells, as an important carrier for the utilization of hydrogen energy, show broad application prospects in transportation, industry, energy storage and other fields. In fuel cells, catalyst materials play a decisive role in the overall performance. Among them, platinum-based catalysts have become the most commonly used cathode oxygen reduction reaction (ORR) catalysts in proton exchange membrane fuel cells (PEMFC) due to their excellent electrocatalytic activity and stability. However, the scarcity of platinum resources and high prices have seriously restricted the large-scale commercial application of fuel cells. Therefore, how to reduce the platinum loading, improve the catalytic efficiency of platinum per unit mass, and achieve large-scale preparation of high-performance platinum-based catalysts through material design and process optimization has become a key issue that needs to be overcome in the current field of hydrogen energy technology.

[0003] To alleviate the cost pressure of pure platinum catalysts, researchers generally adopt an alloying strategy, which involves forming platinum-based intermetallic compounds or solid solution alloy structures with other transition metal elements such as cobalt, nickel, copper, and iron. This alloying method of producing platinum-based alloy catalysts not only effectively adjusts the electronic environment around platinum atoms, thereby enhancing their adsorption and activation of oxygen molecules, but also further optimizes the atomic arrangement on the platinum surface through lattice strain regulation, thereby improving catalytic activity and stability.

[0004] In terms of synthesis and preparation, traditional platinum-based alloy catalysts are mostly synthesized by wet chemical reduction, microwave-assisted method, solvent thermal method or polyol method. These methods can obtain nanoparticles with high specific surface area, uniform metal distribution and good crystal structure under laboratory conditions. However, with the deepening of research, people have gradually realized the technical challenges faced in the process of scaling up from laboratory tests to industrial scale-up. Many methods reported in patents and literatures have shown good catalytic performance in the laboratory stage, such as platinum-cobalt bimetallic alloy catalysts, but it is often difficult to maintain consistency and controllability between batches during scale-up production, resulting in the deviation of key parameters such as crystallinity, particle size distribution, and alloy order of the final product, which in turn affects its catalytic performance.

[0005] On the other hand, some high-performance platinum-based alloy catalysts often rely on complex synthesis steps, such as multi-step heat treatment, template-guided growth, and vapor deposition under high vacuum conditions. While these methods enable precise control of the catalyst's microstructure and composition distribution, they also come with challenges such as large equipment investments, complex processes, and high energy consumption, hindering large-scale continuous production. Furthermore, many patents fail to fully consider the feasibility of industrial implementation when describing their synthesis methods, lacking comprehensive consideration of factors such as precursor cost, reaction time, and operational safety. This makes it difficult for some "high-performance" catalysts to truly achieve industrial application.

[0006] In this context, how to construct a preparation method for platinum-based alloy catalysts that can achieve both high performance and scalability has important practical significance for research and development, so as to meet the actual demand for efficient, stable and low-cost catalysts. Summary of the Invention

[0007] In view of the problems existing in the prior art, the present invention aims to provide a gallium-doped platinum-based ordered alloy catalyst, its preparation method, and use. The gallium-doped platinum-based ordered alloy catalyst comprises a carbon support and active nanoparticles dispersed on the surface of the carbon support; the active nanoparticles comprise an intermetallic ordered alloy composed of Pt and a transition metal M, and the intermetallic ordered alloy is further doped with Ga. By utilizing gallium, an element with a smaller atomic radius for doping, the present invention further shrinks the lattice, thereby modulating the adsorption strength of oxygen reduction reaction intermediates on the Pt surface, thereby effectively improving the catalyst's ORR performance. The resulting catalyst performs better than previously reported platinum-based alloy catalysts of the same type.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a gallium-doped platinum-based ordered alloy catalyst, comprising a carbon support and active nanoparticles dispersed on the surface of the carbon support; the active nanoparticles comprise an intermetallic ordered alloy composed of Pt and a transition metal M, and the intermetallic ordered alloy is further doped with Ga.

[0010] To enhance the ORR activity of the catalyst, the present invention employs gallium doping, replacing, to a certain extent, the transition metal elements M (such as iron, cobalt, nickel, copper, and zinc) in the alloy. Gallium has a smaller atomic radius than transition metals, and its doping within the Pt lattice further shrinks the lattice, thereby modulating the adsorption strength of oxygen reduction reaction intermediates on the Pt surface and improving the ORR performance of the catalyst.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] As a preferred technical solution of the present invention, the carbon carrier includes carbon black; the carbon black includes at least one of EC300-JD, EC600-JD, XC-72 or BP2000.

[0013] Preferably, the average particle size of the active nanoparticles is 2 to 8 nm, for example, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm or 8 nm.

[0014] The gallium-doped platinum-based ordered alloy catalyst (PtMGa / C) of this invention has a controllable particle size, high electrochemical ORR performance, and stability. Furthermore, these nanoparticles have a high specific surface area and electrochemically active area. However, excessively large or small particle sizes can result in a loss of fuel cell performance.

[0015] Preferably, the transition metal M includes at least one of Fe, Co, Ni, Cu or Zn.

[0016] Preferably, based on the mass of the gallium-doped platinum-based ordered alloy catalyst as 100%, the mass of the Pt accounts for 10% to 40%, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38% or 40%, and preferably 25% to 35%; the mass of the transition metal M accounts for 3% to 20%, for example, 3%, 5%, 8%, 10%, 1%, 14%, 16%, 18% or 20%, and preferably 6% to 10%; the mass of the Ga is 10%, 12%, 14%, 16%, 18% or 20%, and preferably 25% to 35%. The amount is 0.01% to 8%, for example, 0.01%, 0.02%, 0.03%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.3%, 5.5%, 5.8%, 6%, 6.3%, 6.5%, 6.8%, 7%, 7.2%, 7.4%, 7.6%, 7.8% or 8%, etc.

[0017] Preferably, the Ga is doped into the crystal lattice of the intermetallic ordered alloy in the form of single atoms.

[0018] In a second aspect, the present invention provides a method for preparing the gallium-doped platinum-based ordered alloy catalyst according to the first aspect, the preparation method comprising:

[0019] Mixing and dispersing a Pt precursor, a transition metal M precursor, a carbon support, and a solvent, and then removing the solvent to obtain a first alloy precursor;

[0020] The obtained first alloy precursor is mixed with a Ga precursor and subjected to ball milling to obtain a second alloy precursor;

[0021] The second alloy precursor is subjected to a first calcination in a reducing atmosphere to obtain a gallium-doped platinum-based ordered alloy catalyst.

[0022] The preparation method of the present invention combines impregnation and ball milling to first prepare a platinum-based alloy precursor (first alloy precursor) by impregnation, then introduce gallium into the platinum-based alloy precursor by a simple ball milling method, and finally convert it into a gallium-doped platinum-based ordered alloy by high-temperature calcination. This method effectively combines large-scale preparation with high activity. The resulting gallium-doped platinum-based alloy catalyst outperforms most reported alloy catalysts of the same type and is of great significance for promoting the development of the hydrogen energy industry. The preparation method requires less manual operation, is simple in process, and is easy to mass produce.

[0023] As a preferred technical solution of the present invention, the Pt precursor includes at least one of chloroplatinic acid, potassium chloroplatinate, platinum acetylacetonate or platinous chloride.

[0024] Preferably, the transition metal M precursor includes at least one of ferric nitrate, ferric sulfate, ferric chloride, ferric acetylacetonate, cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetylacetonate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetylacetonate, copper nitrate, copper sulfate, copper chloride, copper acetylacetonate, zinc nitrate, zinc sulfate, zinc chloride or zinc acetylacetonate.

[0025] Preferably, the solvent includes at least one of deionized water, methanol, ethanol, isopropanol or acetone.

[0026] As a preferred technical solution of the present invention, the mixing and dispersion process includes first ultrasonically dispersing the mixture uniformly and then stirring at room temperature for 6 to 24 hours, for example, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 15 hours, 18 hours, 20 hours, 22 hours or 24 hours.

[0027] Preferably, the method of removing the solvent comprises rotary evaporation drying.

[0028] As a preferred technical solution of the present invention, the Ga precursor includes gallium acetylacetonate.

[0029] Preferably, the rotation speed of the ball mill is 150-600 rpm, for example, 150 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm or 600 rpm.

[0030] Preferably, the ball-to-material mass ratio of the ball mill is (5-20):1, for example, 5:1, 8:1, 10:1, 12:1, 14:1, 16:1, 18:1 or 20:1.

[0031] Preferably, the ball milling time is 0.5 to 6 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h or 6 h.

[0032] As a preferred technical solution of the present invention, the heating rate of the first calcination is 1 to 10°C / min, for example, 1°C / min, 3°C / min, 5°C / min, 8°C / min or 10°C / min, and the temperature is 600 to 950°C, for example, 600°C, 630°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 930°C or 950°C, etc.

[0033] In the present invention, by controlling the heat treatment temperature (the temperature of the first calcination) and the amount of Ga element (the proportion of Ga in the catalyst), it can be ensured that Ga is doped in the lattice of the intermetallic ordered alloy in the form of a single atom.

[0034] Preferably, the reducing atmosphere in the first calcination includes H2, and also includes Ar and / or N2; the volume concentration of H2 is 2% to 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0035] As a preferred technical solution of the present invention, after the first calcination, the obtained gallium-doped platinum-based ordered alloy catalyst is sequentially subjected to acid washing and a second calcination.

[0036] The present invention preferably further performs acid washing and a second calcination. The purpose of the acid washing is to remove the transition metal M atoms on the surface of the active nanoparticles. The second calcination is to reconstruct the arrangement of the surface Pt atomic layer to form a Pt layer on the surface, thereby allowing the active nanoparticles to form a core-shell structure, which is beneficial to improving the stability of the fuel cell ORR reaction.

[0037] Preferably, the pickling temperature is 60-80°C, for example, 60°C, 63°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C or 80°C.

[0038] Preferably, the pickling time is 1 to 2 hours, for example, 1 hour, 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours or 2 hours.

[0039] Preferably, the acid solution used for pickling includes at least one of perchloric acid, sulfuric acid or acetic acid, and the concentration of the acid solution is 0.05-0.2M, for example, 0.05M, 0.08M, 0.1M, 0.12M, 0.14M, 0.16M, 0.18M or 0.2M.

[0040] As a preferred technical solution of the present invention, the second calcination is carried out under a reducing atmosphere, which includes H2 and also includes Ar and / or N2; the volume concentration of H2 is 2% to 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0041] Preferably, the heating rate of the second calcination is 1 to 10°C / min, for example, 1°C / min, 3°C / min, 5°C / min, 8°C / min or 10°C / min, and the temperature is 200 to 500°C, for example, 200°C, 230°C, 250°C, 280°C, 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C or 500°C, etc.

[0042] In a third aspect, the present invention provides a use of the gallium-doped platinum-based ordered alloy catalyst described in the first aspect, wherein the use includes ORR catalytic reaction.

[0043] It should be noted that the present invention does not exhaustively list all applicable point values within the above numerical range, but is not limited to the listed values. Other unlisted values within the above numerical range are also applicable.

[0044] Compared with the existing technical solutions, the present invention has at least the following beneficial effects:

[0045] The present invention uses gallium as the doping element in the alloy catalyst, replacing, to a certain extent, transition metal elements M in the alloy, such as iron, cobalt, nickel, copper, and zinc. Compared to these transition metal elements, gallium has a smaller atomic radius, which can further cause lattice contraction, modulating the adsorption strength of oxygen reduction reaction intermediates on the Pt surface, thereby improving the catalyst's ORR performance. Gallium and transition metal elements also share a similar position in the periodic table. Therefore, compared to doping with other elements, gallium has a negligible effect on the catalyst's particle size, preventing a significant increase in the catalyst's particle size.

[0046] The preparation method of the present invention adopts a combination of impregnation and ball milling to prepare the catalyst, which has less manual operation and mainly relies on a ball mill and magnetic stirring. The process is simple, is less affected by manual operation, and is easy to achieve low-cost, large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the XRD test pattern of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1.

[0048] Figure 2 This is a TEM test image of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1.

[0049] Figure 3 This is a comparison chart of the activities of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1, the commercial PtCo / C catalyst, and the commercial Pt / C catalyst.

[0050] Figure 4 These are the ORR forward scanning polarization curves of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1 in an O2-saturated 0.1 M HClO4 solution initially and after 30,000 cycles of stability testing.

[0051] Figure 5 1 is the cyclic voltammetry curve of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1 after the initial and 30,000 cycle stability tests. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0053] It should be apparent to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0054] Example 1

[0055] This embodiment provides a gallium-doped platinum-based ordered alloy catalyst, comprising a carbon support and active nanoparticles dispersed on the surface of the carbon support; the active nanoparticles comprise an intermetallic ordered alloy composed of Pt and a transition metal M, and the intermetallic ordered alloy is further doped with Ga; the carbon support is carbon black, which is EC300-JD; the transition metal M is Co; the average particle size of the active nanoparticles is 3.8 nm; based on the mass of the gallium-doped platinum-based ordered alloy catalyst being 100%, the mass of Pt accounts for 30.1%; the mass of the transition metal M accounts for 5.7%; the mass of Ga accounts for 2.9%; and the Ga is doped in the lattice of the intermetallic ordered alloy in the form of single atoms.

[0056] The preparation method of the gallium-doped platinum-based ordered alloy catalyst comprises:

[0057] (1) 50 mL of deionized water, 16 mL of a 50 g / L aqueous solution of cobalt chloride, a transition metal M precursor, 27 mL of a 50 g / L aqueous solution of chloroplatinic acid, a Pt precursor, and 1000 mg of carbon black EC300-JD were added to a flask, ultrasonically dispersed, and stirred at room temperature for 12 h; the stirred mixture was evaporated to remove the solvent and dried in a vacuum drying oven at 80 ° C to obtain the first alloy precursor (PtCo / C precursor);

[0058] (2) The first alloy precursor and the Ga precursor gallium acetylacetonate were put into a ball mill at a mass ratio of 30:1, and steel balls were added at a ball-to-material mass ratio of 10:1. The mixture was ball milled at 300 rpm for 1 h to obtain the second alloy precursor;

[0059] (3) The powder of the second alloy precursor obtained by ball milling was subjected to a first calcination at 800°C for 2h at a heating rate of 5°C / min under the condition of 5% hydrogen-argon mixed gas to obtain a gallium-doped platinum-based ordered alloy catalyst (PtCoGa / C alloy catalyst).

[0060] (4) The PtCoGa / C alloy catalyst was placed in a 0.1 M perchloric acid solution, stirred evenly, and then heated to 60°C for 1 hour for acid washing to remove part of the cobalt on the surface of the active nanoparticles. After the reaction was completed, it was washed with deionized water until neutral and then dried. Finally, it was placed at 450°C and 5% hydrogen-argon mixed gas for a second calcination for 1 hour to obtain the final PtCoGa / C alloy catalyst.

[0061] Example 2 to Example 5

[0062] Examples 2 to 5 provide a gallium-doped platinum-based ordered alloy catalyst. By adjusting the amount of Ga precursor in the preparation method, the mass of Ga in the gallium-doped platinum-based ordered alloy catalyst is adjusted from 2.9% to other proportions, as shown in Table 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0063] Example 6

[0064] This embodiment provides a gallium-doped platinum-based ordered alloy catalyst. By adjusting the preparation method, the transition metal M precursor is replaced by cobalt chloride with a corresponding amount of iron nitrate, so that the transition metal M is changed from cobalt to iron, and the amount is controlled so that the mass proportion of the transition metal M is the same as or close to 5.7% in Example 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0065] Example 7

[0066] This embodiment provides a gallium-doped platinum-based ordered alloy catalyst. By adjusting the preparation method, the transition metal M precursor is replaced by cobalt chloride with a corresponding amount of nickel chloride, so that the transition metal M is changed from cobalt to nickel, and the amount is controlled so that the mass proportion of the transition metal M is the same as or close to 5.7% in Example 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0067] Example 8

[0068] This embodiment provides a gallium-doped platinum-based ordered alloy catalyst. By adjusting the preparation method, the transition metal M precursor is replaced by cobalt chloride with a corresponding amount of copper sulfate, so that the transition metal M is changed from cobalt to copper, and the amount is controlled so that the mass proportion of the transition metal M is the same as or close to 5.7% in Example 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0069] Example 9

[0070] This embodiment provides a gallium-doped platinum-based ordered alloy catalyst. By adjusting the preparation method, the transition metal M precursor is replaced by cobalt chloride with a corresponding amount of zinc acetylacetonate, so that the transition metal M is changed from cobalt to zinc, and the amount is controlled so that the mass proportion of the transition metal M is the same as or close to 5.7% in Example 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0071] Example 10

[0072] This embodiment provides a gallium-doped platinum-based ordered alloy catalyst. By adjusting the preparation method, step (4) is not performed, that is, acid washing and the second calcination are not performed. The gallium-doped platinum-based ordered alloy catalyst after the first calcination in step (3) is used for subsequent testing. Except for the above, other conditions are exactly the same as those in Example 1.

[0073] Example 11

[0074] This embodiment provides a gallium-doped platinum-based ordered alloy catalyst. By adjusting step (4) of the preparation method, only acid washing is performed, and after acid washing, the catalyst is dried at 60°C, and the second calcination is not performed. Except for the above, other conditions are exactly the same as those in Example 1.

[0075] Example 12

[0076] This embodiment provides a gallium-doped platinum-based ordered alloy catalyst. By adjusting the amount of Ga precursor and the temperature of the first calcination, the mass content of Ga in the gallium-doped platinum-based ordered alloy catalyst is adjusted from 2.9% to 20%, and the temperature of the first calcination is adjusted from 800°C to 500°C, so that Ga is doped into the lattice of the intermetallic ordered alloy in the form of conventional bulk doping rather than single atoms. Except for the above, other conditions are exactly the same as those in Example 1.

[0077] Comparative Example 1

[0078] This comparative example provides a platinum-based catalyst, which is prepared by adjusting the preparation method so that a Ga precursor is not used for doping, that is, step (2) is not performed, and the first alloy precursor obtained in step (1) is subjected to steps (3) and (4). Except for the above, other conditions are exactly the same as those in Example 1.

[0079] Comparative Example 2

[0080] This comparative example provides a platinum-based catalyst, which is prepared by replacing the Ga precursor with a corresponding amount of transition metal M precursor zinc acetylacetonate in step (2) of the preparation method, and controlling the mass proportion of Zn in the catalyst to be 2.9%. Except for the above, other conditions are exactly the same as those in Example 1.

[0081] Comparative Example 3

[0082] This comparative example provides a platinum-based catalyst, and the preparation method is adjusted in step (1) without using a transition metal M precursor. Except for the above, other conditions are exactly the same as those in Example 1.

[0083] Characterization and testing:

[0084] Ⅰ. Elemental analysis tests were performed on each catalyst, and the results are recorded in Table 1.

[0085] II. X-ray diffraction (XRD) test: The powder sample was evenly flattened in the groove of the quartz plate and placed in the test instrument. The instrument tube voltage and tube current were adjusted to 40kV and 15mA respectively. The test angle was 10° to 90° and the scanning speed was 5° min. -1 .

[0086] Figure 1 This is the XRD test pattern of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1. As can be seen from the figure, no peak representing the Ga lattice appears. Ga forms PtCoGa / C in the form of single atoms. PtCoGa / C is a standard intermetallic ordered alloy and corresponds one-to-one with the standard comparison card.

[0087] III. Figure 2 This is a TEM test image of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1. It can be seen that the PtCoGa / C alloy nanoparticles are uniformly dispersed on the N-doped (N source provided by gallium acetylacetonate) carbon support, with an average particle size of 3.8 nm. The particles are highly dispersed and uniform.

[0088] IV. Rotating disk electrode (RDE) test: 3 mg of catalyst was dispersed in 980 μL isopropanol, 20 μL of 5% Nafion solution was added, and ultrasonication was performed for 1 hour. The dispersed ink was dropped onto a disk (0.2475 cm2 ) electrode, and then fully dried under a baking lamp to produce 40μgPt·cm -2 The electrode head with catalyst loading was used for testing. The specific electrochemical characterization test was carried out in a standard three-electrode system with a carbon rod as the counter electrode and a saturated calomel electrode as the reference electrode. The test was carried out at room temperature. The ORR polarization curve was measured in an O2-saturated 0.1M HClO4 electrolyte, and the background CV curve was measured in an N2-saturated 0.1M HClO4 electrolyte. The specific scanning potential was 0.1~1.1V RHE (V vs. RHE), scan rate is 10 mV·s -1 In addition, commercial PtCo / C alloy catalysts and commercial Pt / C catalysts were prepared for relevant tests for comparison.

[0089] Figure 3 This is a comparison chart of the activities of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1, the commercial PtCo / C catalyst, and the commercial Pt / C catalyst. Figure 4 These are the ORR forward scanning polarization curves of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1 in an O2-saturated 0.1 M HClO4 solution initially and after 30,000 cycles of stability testing. Figure 5 The cyclic voltammetry curves of the gallium-doped platinum-based ordered alloy catalyst obtained in Example 1 are the initial and 30,000 cycle stability tests. The RDE activity and stability tests of Example 1 show that its initial ORR half-wave potential is 0.95 V. After 30,000 cycles of accelerated decay, the half-wave potential decays by 14.3 mV, and the mass specific activity (MA) increases from 1.305 A mg Pt -1 Reduced to 0.908Amg Pt -1 , attenuated by 30.4%, and the area specific activity (SA) increased from 2.145 mA cm -2 Reduced to 1.492 mA·cm -2 , decayed by 30.4%, and the ORR performance before and after decay was much higher than the existing standards. In addition, the ECSA of the catalyst remained unchanged after 30,000 cycles of accelerated decay. It can be seen that the excellent ORR activity exhibited by the catalyst is due to the doping of gallium. The doped gallium element can replace the cobalt element in the crystal lattice to a certain extent. The gallium element with a smaller atomic radius can further cause the lattice to shrink, adjust the adsorption strength of the Pt surface to the oxygen reduction reaction intermediates, and thus improve the ORR performance of the catalyst; further control experiments are carried out on whether the gallium element in the catalyst is doped or not to further verify their role. Using Example 1 as a standard sample, the gallium acetylacetonate added in step 3 is cancelled to synthesize Comparative Example 1, whose particle size is 3.8 nm, consistent with Example 1, but its mass specific activity is 0.968Amg Pt-1 , which is far inferior to Example 1. This comparison shows that the incorporation of gallium has a significant promoting effect on the ORR activity of the catalyst.

[0090] The results of other examples and comparative examples are recorded in Table 1 and Table 2.

[0091] Table 1

[0092]

[0093]

[0094] Table 2

[0095] Group Initial ORR half-wave potential (V) Initial mass specific activity Initial electrochemical specific surface area Example 1 0.95 1.305 60.8 Example 2 0.95 0.967 55.9 Example 3 0.95 0.970 55.3 Example 4 0.93 1.002 54.8 Example 5 0.93 0.989 56.1 Example 6 0.93 1.115 55.4 Example 7 0.93 1.186 53.8 Example 8 0.92 0.993 54.0 Example 9 0.93 1.030 55.1 Example 10 0.93 1.198 51.7 Example 11 0.94 1.230 52.9 Example 12 0.87 0.187 30.2 Comparative Example 1 0.95 0.968 55.1 Comparative Example 2 0.94 0.916 57.1 Comparative Example 3 0.88 0.248 53.0

[0096] It can also be seen from Table 1 and Table 2 that:

[0097] The incorporation of Ga elements can effectively improve the electrochemical properties of PtCo alloys. Only when the Ga incorporation content is within a moderate range can Ga single atoms be formed to play a role in improving the electrochemical properties. As shown in Example 12, when Ga atoms are excessively incorporated, crystalline Ga will be formed, which will fail to improve the electrochemical properties of the alloy. At the same time, pickling and calcination will affect the exposure of Pt activation sites. As shown in Examples 10 and 11, if this treatment procedure is reduced, the degree of improvement in the electrochemical properties of the platinum-based alloy will be affected.

[0098] From the above, it can be seen that the ORR activity of the PtCoGa / C alloy catalyst synthesized in the present invention is higher than that of the commercial Pt / C catalyst and the commercial binary alloy PtCo / C catalyst, and the ORR stability is greatly improved, with the first-cycle mass specific activity reaching up to 1.305Amg Pt -1 After 30,000 cycles of stability testing, the mass specific activity was 0.908Amg Pt -1 , the mass specific activity before and after accelerated decay meets the target. This performance improvement is due to the doping of gallium. Gallium replaces the transition metal elements (iron, cobalt, nickel, copper, and zinc) in the alloy to a certain extent. Compared with these transition metal elements, the atomic radius of gallium is small, which can further cause lattice contraction, adjust the adsorption strength of the Pt surface to the oxygen reduction reaction intermediates, and thus improve the ORR performance of the catalyst; at the same time, the preparation method provided by the present invention mainly relies on impregnation, ball milling and high-temperature calcination. The process is simple and safe, is less affected by manual operation, and is easy to mass produce.

[0099] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the scope of protection of the present invention.

[0100] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any appropriate manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0101] In addition, the various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A gallium-doped platinum-based ordered alloy catalyst, characterized in that: The invention comprises a carbon support and active nanoparticles dispersed on the surface of the carbon support; the active nanoparticles comprise an intermetallic ordered alloy composed of Pt and a transition metal M, and the intermetallic ordered alloy is further doped with Ga.

2. The gallium-doped platinum-based ordered alloy catalyst according to claim 1, characterized in that The carbon support includes carbon black; the carbon black includes at least one of EC300-JD, EC600-JD, XC-72 or BP2000; Preferably, the average particle size of the active nanoparticles is 2 to 8 nm; Preferably, the transition metal M comprises at least one of Fe, Co, Ni, Cu or Zn; Preferably, based on the mass of the gallium-doped platinum-based ordered alloy catalyst being 100%, the mass of Pt accounts for 10% to 40%, preferably 25% to 35%; the mass of the transition metal M accounts for 3% to 20%, preferably 6% to 10%; and the mass of Ga accounts for 0.01% to 8%. Preferably, the Ga is doped into the crystal lattice of the intermetallic ordered alloy in the form of single atoms.

3. A method for preparing the gallium-doped platinum-based ordered alloy catalyst according to claim 1 or 2, characterized in that: The preparation method comprises: Mixing and dispersing a Pt precursor, a transition metal M precursor, a carbon support, and a solvent, and then removing the solvent to obtain a first alloy precursor; The obtained first alloy precursor is mixed with a Ga precursor and subjected to ball milling to obtain a second alloy precursor; The second alloy precursor is subjected to a first calcination in a reducing atmosphere to obtain a gallium-doped platinum-based ordered alloy catalyst.

4. The method for preparing a gallium-doped platinum-based ordered alloy catalyst according to claim 3, characterized in that: The Pt precursor includes at least one of chloroplatinic acid, potassium chloroplatinate, platinum acetylacetonate or platinous chloride; Preferably, the transition metal M precursor includes at least one of ferric nitrate, ferric sulfate, ferric chloride, ferric acetylacetonate, cobalt nitrate, cobalt sulfate, cobalt chloride, cobalt acetylacetonate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetylacetonate, copper nitrate, copper sulfate, copper chloride, copper acetylacetonate, zinc nitrate, zinc sulfate, zinc chloride or zinc acetylacetonate; Preferably, the solvent includes at least one of deionized water, methanol, ethanol, isopropanol or acetone.

5. The method for preparing a gallium-doped platinum-based ordered alloy catalyst according to claim 3 or 4, characterized in that: The mixing and dispersing process includes firstly uniformly dispersing by ultrasonication and then stirring at room temperature for 6 to 24 hours; Preferably, the method of removing the solvent comprises rotary evaporation drying.

6. The method for preparing a gallium-doped platinum-based ordered alloy catalyst according to any one of claims 3 to 5, characterized in that: The Ga precursor includes gallium acetylacetonate; Preferably, the ball milling speed is 150 to 600 rpm; Preferably, the ball-to-material mass ratio of the ball mill is (5-20):1 Preferably, the ball milling time is 0.5 to 6 hours.

7. The method for preparing a gallium-doped platinum-based ordered alloy catalyst according to any one of claims 3 to 6, characterized in that: The first calcination has a heating rate of 1 to 10°C / min and a temperature of 600 to 950°C; Preferably, the reducing atmosphere in the first calcination includes H2, and also includes Ar and / or N2; the volume concentration of H2 is 2% to 10%.

8. The method for preparing a gallium-doped platinum-based ordered alloy catalyst according to any one of claims 3 to 7, characterized in that: After the first calcination, the obtained gallium-doped platinum-based ordered alloy catalyst is sequentially subjected to acid washing and a second calcination; Preferably, the pickling temperature is 60-80°C; Preferably, the pickling time is 1 to 2 hours; Preferably, the acid solution used for pickling includes at least one of perchloric acid, sulfuric acid or acetic acid, and the concentration of the acid solution is 0.05-0.2M.

9. The method for preparing a gallium-doped platinum-based ordered alloy catalyst according to claim 8, characterized in that: The second calcination is carried out in a reducing atmosphere, the reducing atmosphere includes H2, Ar and / or N2; the volume concentration of H2 is 2% to 10%; Preferably, the heating rate of the second calcination is 1-10°C / min and the temperature is 200-500°C; Preferably, the reducing atmosphere in the second calcination includes H2, and also includes Ar and / or N2; the volume concentration of H2 is 2% to 10%.

10. Use of the gallium-doped platinum-based ordered alloy catalyst according to claim 1 or 2, characterized in that: The use includes ORR catalytic reaction.